2018
DOI: 10.1002/joa3.12074
|View full text |Cite
|
Sign up to set email alerts
|

IL‐10(‐592A/C) gene variant a predictor of postoperative atrial fibrillation in the north Indian population

Abstract: BackgroundThere is an accumulating body of evidence indicating a strong association between inflammation and the pathogenesis of atrial fibrillation (AF) in different ethnicities across the globe. AF increases the risk of stroke and heart failure. Despite various researches on IL‐10 response, there is limited clinical evidence present, which demonstrate a role of these immunity regulators in AF. Therefore, this study was designed to decipher the role of IL‐10(‐592A/C) polymorphism in the development of postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Meanwhile, IL-10 produced by Treg cells is a potent anti-inflammatory cytokine (33). A recent study has suggested that IL-10(-592A/C) polymorphism may have a prominent association with postoperative AF (35). Therefore, we reasonably speculate that the increase of Th1/ Treg may associate with the development of RA-AF.…”
Section: Discussionmentioning
confidence: 75%
“…Meanwhile, IL-10 produced by Treg cells is a potent anti-inflammatory cytokine (33). A recent study has suggested that IL-10(-592A/C) polymorphism may have a prominent association with postoperative AF (35). Therefore, we reasonably speculate that the increase of Th1/ Treg may associate with the development of RA-AF.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, the early cytokine changes observed in atrial tissue after treatment with EVs included several pro-inflammatory cytokines known to play a role in the progression of postoperative AF (IL-6, MCP-1, and TGFβ1) [48,49]. Notably, unlike another type of heart-derived cell [50], EDC EVs had no effect on the cardiac content of IL-10, which has been demonstrated to inhibit the development of AF [51][52][53].…”
Section: Effect Of Increasing Ev Doses On Atrial Markers Of Inflammat...mentioning
confidence: 99%